THE USE OF BREAKOUT ROOMS DISCUSSION IN JIGSAW ONLINE LEARNING CLASS: DEVELOPING CREATIVITY AND INCREASING STUDENT ENGAGEMENT - Hirdina Amelia; Rolisda Yosintha (ELTR Journal, 2022)
This study investigates the use of breakout rooms discussion in jigsaw online learning class on developing creativity and increasing student engagement. The reason for establishing this study is how the Breakout Rooms meeting application is suitable for use for the application of the cooperative method learning. This study used a qualitative descriptive research method to collect data from a Likert scale questionnaire ranging from 1 (strongly disagree) to 5 (strongly agree). The research subjects were drawn from a group of college EFL students. This study shows that out of 15 EFL students, The results of participant’ Google forms perceptions about Jigsaw Strategy encourages work together became cooperative learning, showed the response rates of Strongly Agree (SA) 16%, Agree (A) 80%, Neutral (N) 16%, Disagree (D) 8%, and Strongly Disagree (SD) 0%. Meanwhile, the results about breakout rooms on zoom increasing potential of student to be effective as learning media rate of Strongly Agree (SA) 12%, Agree (A) 80%, Neutral (N) 8%, Disagree (D) 0% and Strongly Disagree (SD) 0%. Furthermore the results about students are motivated with Jigsaw Strategy Strongly Agree (SA) 4%, Agree (A) 88% & Neutral (N) 4%, Disagree (D) 4% as well as Strongly Disagree (SD) 0%.